2006
DOI: 10.1271/bbb.70.615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sugars on the Cross-Linking Formation and Phase Separation of High-Pressure Induced Gel of Whey Protein from Bovine Milk

Abstract: The effects of sugars (xylose, arabinose, fucose, fructose, galactose, glucose, sorbitol, maltose, sucrose, and lactose; 0-20% w/v) on the properties of the pressure-induced gel from a whey protein isolate (20%, 800 MPa,30 C, 10 min) were studied. All the sugars decreased the hardness, breaking stress and waterholding capacity of the gel at the same concentration of 55.5 mM. Increasing the sugar content changed the microstructure of the gel from a honeycomb-like structure to a stranded structure, while the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Gel strength also increases with increasing pressure and holding time (Van Camp & Huyghebaert, 1995a;Van Camp et al, 1996). The presence of sugars decreases the extent of intermolecular crosslinking of proteins and restrains phase separation during gelation of whey protein isolate (WPI) under high pressure (He, Azuma, Hagiwara, & Kanno, 2006;Kanno, He, Ametani, & Azuma, 2002). However, there is limited information on the effects of pH and ionic strength (I) on the properties of whey protein gels formed under high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Gel strength also increases with increasing pressure and holding time (Van Camp & Huyghebaert, 1995a;Van Camp et al, 1996). The presence of sugars decreases the extent of intermolecular crosslinking of proteins and restrains phase separation during gelation of whey protein isolate (WPI) under high pressure (He, Azuma, Hagiwara, & Kanno, 2006;Kanno, He, Ametani, & Azuma, 2002). However, there is limited information on the effects of pH and ionic strength (I) on the properties of whey protein gels formed under high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Unfolded β-Lg can interact, through SH/SS interchange reactions, with proteins containing disulfide bonds, e.g. α-La, BSA, and β-Lg [19,25]. Regarding pressure-induced gelation of a WPI solution, the formation of intermolecular S-S bonds between proteins has been confirmed [18,25], and it is likely that the gel is mainly formed by the cross-linking of intermolecular S-S bonds [25].…”
Section: Effects Of Pressure and Protein Concentrationmentioning
confidence: 97%
“…The gelation of protein is influenced in a complex manner by the processes of protein denaturation and aggregation [22,29]. Sugars decrease the degree of intermolecular S-S bonding of proteins [25], and restrain phase separation during the gelation of WPI under high pressure. Fig.…”
Section: Effects Of Sugar Concentrationmentioning
confidence: 99%
“…He et al (2006) reported that monosaccharides and disaccharides, such as xylose, glucose, sucrose, and lactose, decreased the rigidity of the pressure-induced whey protein gel at 800 MPa. They concluded that sugars influenced the characteristics of the pressure-induced gels by inhibiting the intermolecular cross-linking of the proteins and restricting the phase separation of change in the microstructure of the gel from a honeycomb to a thin-stranded structure.…”
Section: Effects Of Saccharides On the Gel Formation Of Proteinsmentioning
confidence: 99%